Characterization of ultrathin gate dielectric films - Leong, Li Ying. (2008)
This study reports on the effect of Fowler-Nordheim injection stress on the gate oxide above the channel and edge (gate/drain overlap) regions. Several methods for electrical characterization of the gate dielectric are used to study the types of charge trapping at the Si-SiO2 interface, channel and edge regions.